2020
DOI: 10.7717/peerj.10096
|View full text |Cite
|
Sign up to set email alerts
|

Novel targets for engineering Physostegia chlorotic mottle and tomato brown rugose fruit virus-resistant tomatoes: in silico prediction of tomato microRNA targets

Abstract: Background Physostegia chlorotic mottle virus (PhCMoV; genus: Alphanucleorhabdovirus, family: Rhabdoviridae) and tomato brown rugose fruit virus (ToBRFV; genus: Tobamovirus, family: Virgaviridae) are newly emerging plant viruses that have a dramatic effect on tomato production. Among various known virus-control strategies, RNAi-mediated defence has shown the potential to protect plants against various pathogens including viral infections. Micro(mi)RNAs play a major role in RNAi-mediated defence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…The ICMV-Ker is a bipartite begomovirus that spread to India and nearby locales in Southeast Asia during the past two decades. Several studies have investigated potential endogenous host-plant mature microRNAs that may target plant viruses based on in silico criteria [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. The miRNAs have evolved as key endogenous biomolecules for regulating gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The ICMV-Ker is a bipartite begomovirus that spread to India and nearby locales in Southeast Asia during the past two decades. Several studies have investigated potential endogenous host-plant mature microRNAs that may target plant viruses based on in silico criteria [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. The miRNAs have evolved as key endogenous biomolecules for regulating gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we have investigated experimentally validated sugarcane genome-encoded mature microRNAs that were predicted to target SCBGAV, SCYLV and SCBV based on in silico criteria [37][38][39]. Several studies have identified complex host-virus interactions and have investigated host-plant miRNAs targeting plant viruses using an in silico approach [97][98][99][100][101][102][103]. The miRNAs have evolved as novel endogenous targets for multiple layers of miRNA-gene level regulation [52,104,105].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested the gene silencing of target viruses using host-delivered miRNAs using computational algorithms. Genome-wide identification and comprehensive analysis of highly potential candidate miRNA targets against plant viruses have therefore been discovered [32][33][34]. The current study was designed by an equal novel computational approach for predicting novel targets against SCYLV in order to combat Polereovirus infection in sugarcane cultivars.…”
Section: Discussionmentioning
confidence: 99%